INTERNAL CONTROL SYSTEM IN COMMERCIAL BANKS, ITS CREATION AND EXISTING PROBLEMS (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes the importance of the internal control system in commercial banks of the Republic of Uzbekistan. Also, the opinions of world scientists in the field of combating the legalization of criminal income are given. International standards and opinions of foreign scientists about the role of the internal control system in the bank's activities are studied and recommendations are made to eliminate the existing shortcomings.